An Evolving Understanding of Sense of Place in Social-Ecological Systems Research and the Barriers and Enablers to its Measurement. - Duggan, Joe; Cvitanovic, Christopher; van Putten, Ingrid (Environmental Management, 2024)
Social-ecological systems (SES) are changing more in the Anthropocene than ever before. With this also comes a change in Sense of Place (SoP), that is, the emotional bond that a person (or group of people) has with a place. This impacts how individuals and groups interact with a place (i.e., their behaviours) and respond to disturbance or change (i.e., their adaptive capacity). To understand how SoP is changing across space and time and to be able to compare this across social-ecological contexts, we must first take stock of how SoP is conceptualised so as to understand how to capture and measure the phenomena in a meaningful way (e.g., to inform policy). Based on in-depth qualitative interviews with leading SoP researchers (n = 17 from 8 countries) this paper aims to identify: (1) the current breadth of theoretical conceptualisations for SoP; (2) the methodologies that have been used to measure SoP in different contexts and settings; and (3) the barriers and (4) enablers to the use of different methodologies. Results show that there has been a change in how SoP has been conceptualised over time, whereby it was traditionally considered as something singular and limited, towards something much more dynamic. Results also show that diverse methods (both quantitative and qualitative) have been used to measure SoP, but the choice of method is often a result of resource constraints that limit research design. These findings suggest that broader collaboration among stakeholders and increased interdisciplinarity would undoubtedly lead to improved outcomes in our understanding of SoP, specifically how it is changing in response to anthropogenic pressures, and how the results can be integrated into policy and practice to support environment conservation and management. It is hoped these findings can help establish a community of practice around how we conceptualise SoP, and hence understand it, to create space for methodological integration and shared learnings as a field.